The Effect of Foam Rolling of the Hamstrings on Proprioception at the Knee and Hip Joints - DAVID, ERIN (Int J Exerc Sci, 2019)
The purpose of this study was to determine the acute effect of hamstring foam rolling on proprioception at the knee and hip joints. Twenty-five participants completed two proprioceptive tests on separate days, in a random order. The joint position matching test used no visual feedback. Participants were verbally guided to a target lunge position, which was maintained for six seconds while right hip and knee angles were recorded. After rest, participants reproduced this position without guidance for six seconds. Three trials were completed at baseline, and zero, 10, and 20 minutes post-intervention. In the force matching test, participants completed three trials with feedback about force output from a graph, and three trials without. They gradually applied knee flexion force against the dynamometer until reaching target force output. This test was also completed at baseline, and zero, 10, and 20 minutes post-intervention. A significant main effect was found for absolute knee position matching error (F(1.97, 47.36), p = 0.004). No significant differences were found between post-intervention values at zero and 10 minutes, zero and 20 minutes, or 10 and 20 minutes for absolute hip position matching error or absolute knee force matching error at zero, 10, or 20 minutes (p > 0.05). Foam rolling improved knee joint position sense for at least 20 minutes post-intervention, and did not decrease hip joint position sense or knee joint force sense. This indicates that foam rolling may be used immediately prior to exercise without the risk of injury due to proprioceptive deficits.